Transformasi Digital BUMDes Tambaknegara Berkarya dalam Optimalisasi Pengelolaan Pariwisata - Luzi Dwi Oktaviana; Ilham Albana; Septi Fajarwati; Anugerah Bagus Wijaya; Zanuar Rifai; Fiby Nur Afiana (Universitas Pahlawan Tuanku Tambusai, 2026)
Sorjem (Ngisor Jembatan) is a leading tourism destination in Tambaknegara Village, located along the Serayu River. It offers nature- and culture-based attractions, including river cruises, local culinary experiences, and interactions with local traditions. Managed by the Village-Owned Enterprise (BUMDes) “Tambaknegara Berkarya,” the destination faces challenges related to fragmented tourism service management and limited promotional activities. To address these issues, a Community Service Program (PKM) conducted by Universitas Amikom Purwokerto and funded by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) in 2025 was implemented. The program produced an integrated tourism management website covering ticketing, boat rentals, and culinary services, strengthened social media promotion through regular content updates, and improved the BUMDes organizational structure by establishing a dedicated tourism division. Conducted from July to December 2025, the program aimed to enhance tourism management, increase promotional capacity, and strengthen institutional support for sustainable village tourism development.